Decoding sustainable growth: The role of digital technology and entrepreneurship in carbon reduction - Zeeshan Arshad; Mara Madaleno; Ana I Lillebø; Helena Vieira (Sustainable Technology and Entrepreneurship)
Entrepreneurship is instrumental in promoting innovation towards sustainable economic growth. Through information and communication technology (ICT) access and development, digitalization enhances entrepreneurship, fostering the path to sustainable economic growth. However, the literature results evidenced thus far are mixed and do not consider simultaneously the exploration of these cumulative relationships, a gap the present article tries to fill in. Herein is explored the relationship between entrepreneurial activities, ICT, energy consumption, economic growth, and environmental degradation, examining the impact of digitalization and entrepreneurial activities on carbon degradation, with the corresponding effect on the environment, considering a panel of 16 EU countries between 2001 and 2020, using cross-sectional and causality models to account for short and long-run effects. This study also validates these economies' Environmental Kuznets Curve (EKC) while finding critical cross-sectional dependencies. Despite finding that ICT and entrepreneurial activities improved environmental quality, our work points out that ICT and entrepreneurial activities deteriorated the environment. All the macroeconomic variables evidence long-run relationships with carbon degradation or environmental quality. However, no causality is found between ICT and economic growth, nor between entrepreneurship and economic growth, therefore challenging the idea that growth boosts ICT or entrepreneurship activities in EU countries. Important policy directions are presented considering the results that may foster better routes to sustainable growth and development for EU countries.